2021
DOI: 10.1073/pnas.2104511118
|View full text |Cite
|
Sign up to set email alerts
|

DNA-inspired nanomaterials for enhanced endosomal escape

Abstract: To realize RNA interference (RNAi) therapeutics, it is necessary to deliver therapeutic RNAs (such as small interfering RNA or siRNA) into cell cytoplasm. A major challenge of RNAi therapeutics is the endosomal entrapment of the delivered siRNA. In this study, we developed a family of delivery vehicles called Janus base nanopieces (NPs). They are rod-shaped nanoparticles formed by bundles of Janus base nanotubes (JBNTs) with RNA cargoes incorporated inside via charge interactions. JBNTs are formed by noncovale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 11 publications
1
45
0
Order By: Relevance
“…RNA interference (RNAi) therapies, including siRNA, require a nanocarrier to shield the sensitive and negatively charged interfaces of the siRNA strands that make delivery into cellular membranes and ECM difficult [ 90 ]. A previously discussed approach for siRNA delivery consisted of the small interfering RNA being “sandwiched” between JBNt strands, with the short and slim morphologies of the delivery vehicles resulting in increased penetration to extracellular matrices [ 91 , 92 ]. This structure was eventually termed a “Nanopiece,” which has the diameter of a tubular structure, being ~20 nm, and a positive ionic charge that makes it uniquely qualified for penetrating the ECM for the purpose of gene delivery into hard-to-reach areas.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…RNA interference (RNAi) therapies, including siRNA, require a nanocarrier to shield the sensitive and negatively charged interfaces of the siRNA strands that make delivery into cellular membranes and ECM difficult [ 90 ]. A previously discussed approach for siRNA delivery consisted of the small interfering RNA being “sandwiched” between JBNt strands, with the short and slim morphologies of the delivery vehicles resulting in increased penetration to extracellular matrices [ 91 , 92 ]. This structure was eventually termed a “Nanopiece,” which has the diameter of a tubular structure, being ~20 nm, and a positive ionic charge that makes it uniquely qualified for penetrating the ECM for the purpose of gene delivery into hard-to-reach areas.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Another study by Lee et al used the JBNps to enter the cellular membrane via macropinocytosis to successfully deliver siRNA, where the JBNps can then escape from endosomes using a “proton sponge” effect ( Figure 6 ). This has shown promise in replacing the use of cationic polymers, which usually have low biodegradability and biocompatibility, due to the JBNps DNA-mimicking chemistry and noncovalent bonds [ 92 ]. JBNps also express superior uptake efficiency and penetration similar to lipid nanoparticles (LNPs), such as lipofectamine.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid-based nanoparticles have been used for the delivery of antigens including nucleic acids and proteins of infectious agents as well as cancer therapeutic agents to induce humoral immune responses (Aldosari et al, 2021;Lee et al, 2021;Park et al, 2021). These lipid-based nanocarriers pass through the cell membrane for cellular uptake by macropinocytosis, a type of endocytosis where they must escape from the endosomal lumen to deliver their enclosed antigens into the cytosol (Guevara et al, 2020;Lee et al, 2021).…”
Section: Lipid-based Nanoparticlesmentioning
confidence: 99%
“…Lipid-based nanoparticles have been used for the delivery of antigens including nucleic acids and proteins of infectious agents as well as cancer therapeutic agents to induce humoral immune responses (Aldosari et al, 2021;Lee et al, 2021;Park et al, 2021). These lipid-based nanocarriers pass through the cell membrane for cellular uptake by macropinocytosis, a type of endocytosis where they must escape from the endosomal lumen to deliver their enclosed antigens into the cytosol (Guevara et al, 2020;Lee et al, 2021). While ionizable lipid pK a was thought to be the main factor involved in driving lipid nanoparticle potency and tolerability due to its effects on opsonization of the particles, cellular uptake and endosomal escape efficiency, it has been shown that other factors play a role in the immunogenicity of lipid nanoparticles (Hassett et al, 2019).…”
Section: Lipid-based Nanoparticlesmentioning
confidence: 99%